Pengaruh ROA, CR, Sales Growth, Dan DPR Terhadap Harga Saham Perusahaan Manufaktur - Ivan Octavianus, Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study was to analyze the effect of return on asset, current ratio, sales growth and dividend payout ratio on stock price on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The data used in this study were 96 by using purposive sampling techniques. Eviews version 10.0 is used in this study. Simultaneously return on asset, current ratio, sales growth and dividend payout ratio have a significant effect together on stock price. Partially the result of this study indicate that current ratio and sales growth have a negative and significane effect on stock price. While return on asset and dividend payout ratio hav negative ande no significant on stock price.